Pengaruh Perendaman Larutan Kalsium Klorida Terhadap Sifat Fisik Dan Tingkat Kesukaan French Fries Labu Kuning (Cucurbita moschata Durch) (Effect of Calcium Chloride Solution Immersion on Physical Characteristic and Hedonic Scale of Pumpkin French Fries (Cucurbita moschata L.) - Diah Kartikawati; Dyah Ilminingtyas; Nurtekto Nurtekto (FEB UNTAG Semarang, 2017)
Pumpkin contains nutrients that are complete enough with carbohydrates, protein, some minerals such as calcium, phosphorus, iron, and vitamins are vitamin B and C and fiber. Yellow or orange flesh indicated very high carotenoid content and had potential to be processed into one kind of food product frozen french fries. The purpose of this study was to determine the optimum concentration of CaCl2 to produce french fries pumpkins. The study design was completely randomized with 4 treatments CaCl2 concentration, 0%, 0.5%, 1% and 1.5%. The test was done on the physical properties of texture and color, and organoleptic properties include taste, color and aroma. The results showed that the use of a solution of 1% and 1.5 CaCl2 generate texture higher than 0.5% CaCl2; The highest brightness and color value in the treatment without the addition of CaCl2. Keywords: pumpkin french fries, blanching, CaCl2